2017
DOI: 10.1186/s13072-017-0169-6
|View full text |Cite
|
Sign up to set email alerts
|

A screening system to identify transcription factors that induce binding site-directed DNA demethylation

Abstract: BackgroundDNA methylation is a fundamental epigenetic modification that is involved in many biological systems such as differentiation and disease. We and others recently showed that some transcription factors (TFs) are involved in the site-specific determination of DNA demethylation in a binding site-directed manner, although the reports of such TFs are limited.ResultsHere, we develop a screening system to identify TFs that induce binding site-directed DNA methylation changes. The system involves the ectopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 54 publications
(53 reference statements)
9
33
0
Order By: Relevance
“…A recent survey of the mutations occurring within the T-box domain in those TBX genes known to cause the different genetic syndromes did show that they abrogate either the interaction with the known methyl or dimethyl transferases ( 47 ). However, the direct supporting evidence to our data came from a study that showed using a newly described screening system that TBX5 is one of few transcription factors that induce binding site-directed DNA demethylation ( 49 ). These findings coupled to the global methylation process that underscores all lung cancer subtypes and mainly the nicotine-induced types will thus potentially position the effect of the for TBX genes in the pathway that includes demethylating agent in clinical trials like 5-AZA ( 50 , 51 ).…”
Section: Discussionsupporting
confidence: 71%
“…A recent survey of the mutations occurring within the T-box domain in those TBX genes known to cause the different genetic syndromes did show that they abrogate either the interaction with the known methyl or dimethyl transferases ( 47 ). However, the direct supporting evidence to our data came from a study that showed using a newly described screening system that TBX5 is one of few transcription factors that induce binding site-directed DNA demethylation ( 49 ). These findings coupled to the global methylation process that underscores all lung cancer subtypes and mainly the nicotine-induced types will thus potentially position the effect of the for TBX genes in the pathway that includes demethylating agent in clinical trials like 5-AZA ( 50 , 51 ).…”
Section: Discussionsupporting
confidence: 71%
“…To our knowledge, this is the first report of RUNX3 involved in LTR activation. There has also been recent report that RUNX3 can induced site-specific DNA hypomethylation (Suzuki et al 2017). Along with our finding that RUNX3 binds to >50% of all EBV-activated LTRs, EBVinduced RUNX3 activity may be an important factor in the hypomethylation of EBV-activated LTRs.…”
Section: Discussionsupporting
confidence: 89%
“…Although this is better supported at the level of pioneer factors, it is feasible that other TFs involved in lineage commitment are also able to recruit TETs to specific genomic loci. While several TFs are involved in DNA demethylation by interacting with TET proteins (e.g., Nanog during establishment of pluripotency [101], the hematopoiesis-related RUNX1 [102] and EBF1 [103], PU.1 in osteoclast differentiation [104], and PPARγ in adipogenesis [105]), screening systems suggest that many others may share this property [106]. Alternatively, enhancer elements that distinguish cell types may be specifically targeted by TETs based on their chromatin conformation and histone mark profile.…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%